1994
DOI: 10.1002/j.1552-4604.1994.tb03983.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Intravenous OPC‐18790 in Humans: A Novel Nonglycosidic Inotropic Agent

Abstract: OPC-18790, a nonglycosidic intropic agent, is now under clinical development for treatment of congestive heart failure. Two separate studies (one placebo-controlled) were conducted to evaluate its pharmacokinetics and pharmacodynamics after intravenous administration to a total of 36 healthy male subjects. The drug was administered both rapidly as a .05-, .1-, .2-, or .4-mg/kg intravenous dose, and as a 1-hour infusion of .5, 1.0, 2.5, 5.0, 10.0, or 15.0 micrograms/kg/minute. Echocardiograms (ECHO) were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Therefore, it is concluded that the vascular relaxing effects of toborinone may be mediated by both the PDE III inhibitory action and the weak adrenaline α-receptor blocking activities. In clinical trials, 19 the therapeutic plasma concentration of toborinone was about 800 ng/ml after 60 min of continuous intravenous infusion at 10 µg/kg per min. This concentration is approximately equivalent to the EC 50 values obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is concluded that the vascular relaxing effects of toborinone may be mediated by both the PDE III inhibitory action and the weak adrenaline α-receptor blocking activities. In clinical trials, 19 the therapeutic plasma concentration of toborinone was about 800 ng/ml after 60 min of continuous intravenous infusion at 10 µg/kg per min. This concentration is approximately equivalent to the EC 50 values obtained in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The drug's mechanism of action includes an inhibitory action on phosphodiesterase III, an inhibitory action on the potassium channel, and a prolonging effect on action potential duration. Previous studies have shown toborinone to have beneficial hemodynamic effects in animals [2] and in normal volunteers [3] without increasing myocardial oxygen consumption and in dilated cardiomyopathy without changing heart rate [4]. We therefore investigated the effectiveness, usefulness, and safety of this drug for the treatment of heart failure occurring immediately after extracorporeal circulation (ECC) in cardiac surgery, and the relationship between infusion volume and hemodynamics was also examined.…”
Section: Introductionmentioning
confidence: 99%